Early efficacy and safety data with fixed‐dose combination calcipotriol/betamethasone dipropionate foam attributed to mechanism of absorption and steroid potency. Issue Volume 35:Issue S1(2021)Supplement (23rd February 2021) - Tada, Y.; Iversen, L.; Koo, J.
Abstract: Topical therapy is the mainstay of treatment for the majority of patients with psoriasis vulgaris (chronic plaque psoriasis), with combinations of vitamin D analogues and glucocorticoids having been shown to negate many of the negative effects associated with either monocomponent individually. Following the established efficacy of fixed‐dose combination calcipotriol (Cal; 50 µg/g) plus betamethasone dipropionate (BD; 0.5 mg/g) ointment and gel formulations, a novel Cal/BD foam formulation was developed. When applied, Cal/BD foam forms a supersaturated solution on the skin, increasing the penetration and bioavailability of Cal and BD. Early data indicate that this results in improved efficacy outcomes versus Cal/BD ointment, without negatively affecting safety outcomes (such as the incidence/severity of side effects or impacted calcium homeostasis or hypothalamic‐pituitary‐adrenal axis). This article discusses the potency and absorption of fixed‐dose combination Cal/BD foam, as well as the positive early efficacy and safety data associated with its utilisation in the treatment of psoriasis vulgaris. Abstract : Video abstract